Evidence on the nature and origins of endosperm dosage requirements in Solanum and other angiosperm genera - Ehlenfeldt, M.K.; Ortíz, R. (1995)
Success of seed development following sexual crosses is primarily dependent on proper endosperm function and development. The failure to produce triploids, or “triploid block” in 4x×2x crosses served as the impetus for numerous studies of embryo and endosperm to attempt to explain cross failure. Early explanations were based upon a concept of a 2∶3∶2 ploidy balance between maternal tissue, endosperm, and embryo. Subsequent studies done with maize demonstrated that normal endosperm development in intraspecific maize crosses is dependent solely on having a 2∶1 maternal to paternal genome dosage in the endosperm. These results have been modified and extended to solanaceous species in the form of an endosperm dosage system in which empirically determined factors must bear the same 2∶1 relationship for crosses to succeed. Crossing behavior of these species suggest that the system is polygenically controlled and regulates both interspecific and intraspecific crosses. Endosperm dosage systems explain many aspects of species evolution, but the system appears to have originated as an ancient means of ensuring diploid fidelity.